2015
DOI: 10.1002/path.4492
|View full text |Cite
|
Sign up to set email alerts
|

CUL4B activates Wnt/β‐catenin signalling in hepatocellular carcinoma by repressing Wnt antagonists

Abstract: Activation of Wnt/β-catenin signalling is frequently observed in many types of cancer including hepatocellular carcinoma (HCC). We recently reported that cullin 4B (CUL4B), a scaffold protein that assembles CRL4B ubiquitin ligase complexes, is overexpressed in many types of solid tumours and contributes to epigenetic silencing of tumour suppressors. In this study, we characterized the function of CUL4B in HCC and investigated whether CUL4B is involved in the regulation of Wnt/β-catenin signalling. CUL4B and β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 46 publications
4
68
0
1
Order By: Relevance
“…Wnt/β-catenin signaling pathway has been demonstrated abnormal activated in many kinds of cancer [55–57]. At present, Yuan et al [19] found CUL4B functioned as a positively regulator in Wnt/β-catenin signaling in HCC. CUL4B and β-catenin are over-expressed in HCC tissues and have positive correlation.…”
Section: Cul4b Related Signaling Pathwaysmentioning
confidence: 99%
“…Wnt/β-catenin signaling pathway has been demonstrated abnormal activated in many kinds of cancer [55–57]. At present, Yuan et al [19] found CUL4B functioned as a positively regulator in Wnt/β-catenin signaling in HCC. CUL4B and β-catenin are over-expressed in HCC tissues and have positive correlation.…”
Section: Cul4b Related Signaling Pathwaysmentioning
confidence: 99%
“…CUL4B has recently been shown to be highly expressed in a variety of human malignancy and is positively correlated with tumor progression (25,26,29,39,40). In the current study, we demonstrated that CUL4B functions to limit the expansion and activity of MDSCs that are an integral part of the immunosuppressive tumor microenvironment.…”
Section: Discussionmentioning
confidence: 57%
“…Our recent study showed that CUL4B could activate Wnt/b-catenin signaling in human hepatocellular carcinoma (29). Thus, we next examined the effect of Cul4b ablation on the level of b-catenin in MDSCs.…”
Section: Aberrant Accumulation Of Mdscs Was Mediated By Downregulatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Up to half of HCC patients have activation of Wnt/β-catenin signaling pathway [31,32,33]. When Wnt signaling is suppressed, generally due to a combination of lack of Wnt ligands and a prevalence of Wnt antagonists, β-catenin is sequentially phosphorylated by CK1 and GSK3β [34].…”
Section: Wnt/β-catenin Signaling and Epigeneticsmentioning
confidence: 99%